Improving control over euthanasia of persons with psychiatric illness: Lessons from the first Belgian criminal court case concerning euthanasia - De Hert, Marc; Loos, Sien; Sterckx, Sigrid; Thys, Erik; Van Assche, Kristof (Frontiers in Psychiatry, 2022)
Background Belgium is one of very few countries that legally allow euthanasia for suffering caused by psychiatric illness. In the first criminal trial in Belgium of physicians involved in euthanasia, three physicians recently faced the accusation of “murder by poisoning,” for allegedly having failed to comply with several requirements of the Belgian Euthanasia Law in granting the euthanasia request a woman suffering from psychiatric illness. Although all three physicians were acquitted, the case generated much debate among policy makers, medical professionals, and the general public. Method We use this trial as the starting point for a critical analysis of the adequacy of the three-level control system established in the Euthanasia Law, as it is applied in the evaluation of euthanasia requests from persons who suffer unbearably from a psychiatric illness. This analysis is based on information presented during the criminal trial as well as information on the euthanasia that was published in the press. Results Our analysis highlights substantial problems in the assessment and granting of the euthanasia request. The patient was euthanized without it having been substantiated that her psychiatric illness had no prospect of improvement and that her suffering could not be alleviated. The three-step control system enshrined in the Law and promoted by the Federal Control and Evaluation Commission for Euthanasia appears to have failed at each level. Conclusion To evaluate requests for euthanasia for mental suffering caused by psychiatric illness, the requirements of the Belgian Euthanasia Law should be complemented by mandating the advice of two psychiatrists, and face-to-face discussions between all physicians involved. In parallel with the process of evaluating the euthanasia request, a treatment track should be guaranteed where reasonable evidence-based treatments and recovery-oriented options are tried.